Advanced engineering fluid mechanics - Muralidhar, K.; Biswas, Gautam (Oxford, U.K. : Alpha Science International Ltd., 2015)
This work marks the centenary of the rediscovery of Mendel's laws of biological inheritance, which have had their greatest economic impact on the rapid development of plant breeding. The concepts and methodology of plant breeding with their underpinning of advances in classical and molecular genetics and biotechnology have received special attention. The monograph, thus, documents the developments of methods of plant breeding over a period of 100 years beginning with some of the landmark discoveries in classical and molecular genetics. Plant breeding in the 21st century will be marked by increasing integration of the current methods with the newer techniques of modern biotechnology, this book points to the kind of integration which will be taking place. molecular cytogenetics; transposable elements; chromosome manipulations; host-pathogen interactions; quantitative trait loci; simple and recurrent selection methods; heterosis breeding; mutation breeding; plant genetic resources and intellectual property rights; plant genomics; and molecular approaches in crop improvement. This book contains papers that revisit some of the landmark discoveries in genetics and plant breeding.
Includes bibliographical references and index.
Keywords: Fluid mechanics; Fluid mechanics -- Mathematics